Development of Conductive Nanocomposite for Sensing Application - Prasad, Brijesh; Panwar, Varij; Chaturvedi, Mayank; Rathi, Vikash; S. Gill, F; Sharma, Kapil; P.Patil, Pravin; ., . (International Journal of Engineering and Technology, 2018)
Carbonaceous compounds being conductive in nature have proved themselves as the best conductive network assembly material with Poly (vinylidene fluoride) (PVDF) polymer matrix which forms dielectric medium. Carbon based compounds are conductive in nature and are being usedÂ to form conductive channels for the flow of charge for the application of health as soft electronic devices and smart flexible conducting thin films in the form of sensors and actuators. Carbon nano fibers (CNF) play role of conductive filler to form conductive networks for the flow of charge in the polymer matrix. The interesting thing about CNF is its tailorable concentration. It influences the mechanical and electrical properties with different weight percent. In the present study solvent casting technique is used for the development of composite membrane, which is easy to fabricate and less costly. An increase in CNF content leads to deterioration of youngâ€™s modulus in comparison with pure PVDF, while with the infiltration of CNF in different quantities increases toughness and overall mechanical strength of the polymer composite of PVDF-CNF. CNF helped in increasing the electrical conductivity of the samples by entrapping in between the matrix and helping in bridge formation for the charge flow. The obtained conductive membrane showed low resistance, good electrical properties and high conductivity. The conductive film can be utilized as a conductive medium as it was able to glow the LED bulb at very low voltage of 2 V with drop of 1.8 V.Â Â